BUSINESS DIGITALIZATION TRAINING: Optimization of Digital Business Opportunities and Advantages - Rezky Fajar Pambudi; Endang Kustini (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Uncertainty in economic conditions can be caused by many factors, one of which is the Covid-19 pandemic. Many companies have gone out of business, because they were unable to overcome the negative impact. This becomes a lesson for business actors, especially in Indonesia, about the uncertainty of economic conditions. Based on this, this training activity is an effort from the academic side of Pakuan University to provide vocational school graduates with knowledge about running a business. Thus, they get referrals as provision/preparation for running a business in the future. The object of the service activity was carried out in the city of Bogor, which was attended by 150 participants from vocational school graduates in the city of Bogor. The method of this activity is presentation and discussion, namely explaining economic conditions, the impact of economic uncertainty and solutions to overcome problems. As a result of this activity, the participants received information on how to deal with economic uncertainty through the concept of business digitization. This activity explained the opportunities and benefits of using digital media as a solution to maintaining a business existence in the midst of economic uncertainty due to the pandemic and globalization.